Tradisi Upacara Pasola dalam Kebudayaan Masyarakat Sumba sebagai Ide Penciptaan Boardgame - Iis Hannani (Jurnal Pendidikan dan Penciptaan Seni, 2021)
The purpose of writing this article is to describe the process of creating a board game that makes the Pasola Ceremony a source of ideas. The Pasola ceremony is one of the cultures originating from eastern Indonesia, namely Sumba, East Nusa Tenggara. This ceremony is part of a series of cultural rituals carried out by the Sumba people who still adhere to the Merapu belief. Therefore, Pasola is a cultural wealth of Indonesia that must be preserved and preserved as a wealth of ancestral heritage. This is a source of inspiration in realizing ideas and ideas, so that they are translated into board game works. The process of creating this board game is adapting from the method of designing the work created by the author. The first stage is to explore the data to be the source of the creation idea. The second stage, deepening the source of ideas and determining the form of the work. The third stage, the form exploration process to enrich the design. The fourth stage enters the creation stage and the last stage is finishing. The visualized work is in the form of an integral part of the Pasola Boardgame.